2005
DOI: 10.1101/gad.1321305
|View full text |Cite
|
Sign up to set email alerts
|

Elevated telomere-telomere recombination in WRN-deficient, telomere dysfunctional cells promotes escape from senescence and engagement of the ALT pathway

Abstract: Werner Syndrome (WS) is characterized by premature aging, genomic instability, and cancer. The combined impact of WRN helicase deficiency and limiting telomere reserves is central to disease pathogenesis. Here, we report that cells doubly deficient for telomerase and WRN helicase show chromosomal aberrations and elevated recombination rates between telomeres of sister chromatids. Somatic reconstitution of WRN function, but not a WRN helicase-deficient mutant, abolished telomere sister chromatid exchange (T-SCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
156
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(166 citation statements)
references
References 52 publications
9
156
1
Order By: Relevance
“…The results presented in this paper also support earlier findings and provide further evidence for the role of BRCA1 in telomere homeostasis. Similarly to cells lacking BLM and WRN, proteins affected in Bloom and Werner syndrome patients (Salk et al, 1985; Laud et al, 2005), we have shown that BRCA1 defective cells harbor high frequencies of T‐SCEs (Figs. 1A and 3A).…”
Section: Discussionsupporting
confidence: 69%
“…The results presented in this paper also support earlier findings and provide further evidence for the role of BRCA1 in telomere homeostasis. Similarly to cells lacking BLM and WRN, proteins affected in Bloom and Werner syndrome patients (Salk et al, 1985; Laud et al, 2005), we have shown that BRCA1 defective cells harbor high frequencies of T‐SCEs (Figs. 1A and 3A).…”
Section: Discussionsupporting
confidence: 69%
“…In the first case, it is known that the WRN protein interacts with several telomere proteins and unwinds a telomeric D-loop structure (35). Furthermore, the loss of WRN function facilitates the activation of the alternative lengthening of telomeres mechanism, which may engender cancer-relevant chromosomal aberrations and tumor formation in mouse models (36). Interestingly, alternative lengthening of telomeres is commonly observed in sarcomas, where we have also observed WRN hypermethylation and which are characteristic of patients with WS.…”
Section: Discussionmentioning
confidence: 75%
“…Telomerase-independent telomere maintenance that results in telomeres of normal length has been reported for primary and lymphoma cells from mouse telomerase RNA mutants (33), although other studies have revealed long and heterogeneous telomeres in mouse tumors derived in the context of telomerase deficiency (34,35). One immortalized human cell line, C3-cl6, maintained short and homogeneous telomeres in the absence of telomerase (10).…”
Section: Pot-2 Represses a Distinct Form Of Alt With Telomeres Of Normalmentioning
confidence: 99%